2018
DOI: 10.1371/journal.pcbi.1006398
|View full text |Cite
|
Sign up to set email alerts
|

Selective ion permeation involves complexation with carboxylates and lysine in a model human sodium channel

Abstract: Bacterial and human voltage-gated sodium channels (Navs) exhibit similar cation selectivity, despite their distinct EEEE and DEKA selectivity filter signature sequences. Recent high-resolution structures for bacterial Navs have allowed us to learn about ion conduction mechanisms in these simpler homo-tetrameric channels, but our understanding of the function of their mammalian counterparts remains limited. To probe these conduction mechanisms, a model of the human Nav1.2 channel has been constructed by graftin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
73
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(75 citation statements)
references
References 82 publications
2
73
0
Order By: Relevance
“…A cationic Lys residue in the DEKA ring was also found to be crucial for the Na + conduction mechanism and Na + /K + selectivity in those studies, in particular participating in the knock‐on mechanism similarly to a permeating Na + ion (Flood et al . ). No doubt future studies of the structural differences between prokaryotic and eukaryotic ion channels will bring about new understanding of ion permeation in sodium channels of different organisms, but extrapolating these findings to eukaryotic Na V channel function due to their complexities remains a formidable task.…”
Section: Ion Conductionmentioning
confidence: 97%
See 1 more Smart Citation
“…A cationic Lys residue in the DEKA ring was also found to be crucial for the Na + conduction mechanism and Na + /K + selectivity in those studies, in particular participating in the knock‐on mechanism similarly to a permeating Na + ion (Flood et al . ). No doubt future studies of the structural differences between prokaryotic and eukaryotic ion channels will bring about new understanding of ion permeation in sodium channels of different organisms, but extrapolating these findings to eukaryotic Na V channel function due to their complexities remains a formidable task.…”
Section: Ion Conductionmentioning
confidence: 97%
“…Their SFs display asymmetries with aspartic acid, glutamic acid, lysine and alanine (DEKA) from different channel domains forming Na + binding site Site HFS compared to the EEEE ring in prokaryotic channels. Several recent MD studies used eukaryotic Na V homology models (Mahdavi & Kuyucak, 2015;Ahmed et al 2017), hybrid models with a grafted SF eukaryotic Na V channel SF onto bacterial structures (Li et al 2017b;Flood et al 2018) as well as new Na V PaS structure . These studies identified a unique asymmetric Na + permeation pathway involving coordination with Asp and Glu residues in the DEKA ring as well as in the outer SF.…”
Section: Ion Movement Across K + Channel Selectivity Filtermentioning
confidence: 99%
“…Importantly, while the full permeation process across NavAb is known to rely on multi-ion occupancy 17,18,22,30,37 , using 1D-PMFs appears to provide an idealized “effective” cation binding profile, which captures essential features and provides qualitative correlation with certain experimental results. This may resemble the infinite dilution situation – a common reference state for thermodynamic models of membrane transport 38 .…”
Section: Resultsmentioning
confidence: 99%
“…In the Cryo-EM structure of the eukaryotic (putative) Nav channel (NavPaS) 12 from the American cockroach ( Periplaneta americana ), the DEKA selectivity filter is a few Å more constricted than its prokaryotic counterparts, nevertheless it is larger than Hille’s estimates for the frog node Nav SF. Despite of a relatively large selectivity filter, the sidechains of the acidic and lysine residues can stretch out 4–6 Å away from the backbone and appear to be sufficiently dynamic to reach out to either the opposite or proximal sidechains, effectively decreasing the cross-sectional area of the filter 17,18 , thus dynamically lowering ionic flux. In particular, movements of the glutamate sidechains appear to be able to create an efficient blockage by potassium ions 17,19,20 directly supporting mechanisms proposed by French and collaborators in 1994 21 .…”
Section: Introductionmentioning
confidence: 99%
“…We have created a new tool for the investigation of Na + channels that will enable the physical construction and electrophysiological investigation of bacterial channels (with atomic-resolution structure) exhibiting a SF, for example, composed of an amino acid motif (DEKA) typical of eukaryotic Nav channels. For instance, Flood et al [24] recently simulated Na + permeation in a simulation model of the human Nav1.2 channel constructed by grafting residues of its selectivity filter and external vestibule region onto a bacterial channel with atomic-resolution structure. Their simulations captured a Na + knock on conduction mechanism in which the DEKA ring lysine (in its protonated form) was seen to form a stable complex with carboxylates and Na + .…”
Section: Discussionmentioning
confidence: 99%